The impact of RAN sharing - Marc Ivaldi; Louise Aimene; Francois Jeanjean; Julienne Liang (International Telecommunications Society (ITS), 2021)
In this paper, we formulate and estimate a structural model of demand to analyse the equilibrium effect of the RAN sharing by using cross-country panel data in 28 EU countries in years 2010-2020. Based on model estimates, our simulation analysis in Spain firstly provides a quantitative assessment of the impact of RAN sharing on mobile operators. We find that prices decrease for mobile operators involved in RAN sharing agreement due to cost reductions. In a competitive environment where operators compete, MNOs not involved in RAN sharing also lower their prices in a Nash equilibrium. We further evaluate the consumer welfare consequence of the presence of RAN sharing, and find that the RAN sharing enhanced the consumer surplus by generating lower prices for all mobile operators.
Keywords: L40; L96; L11; 330; Mobile telecommunications; network sharing; competition; consumer welfare